Curcumae Rhizoma - combined with Sparganii Rhizoma in the treatment of liver cancer: Chemical analysis using UPLC-LTQ-Orbitrap MSn, network analysis, and experimental assessment - Jing Wei; Jing Wei; Xiaoping Wang; Xiaoping Wang; Ying Dong; Ying Dong; Xiangjian Zhong; Xiangjian Zhong; Xueyang Ren; Xueyang Ren; Ruolan Song; Ruolan Song; et al. (Frontiers Media S.A., 2022)
Objective:Curcumae Rhizoma-Sparganii Rhizoma (CR-SR) is a traditional botanical drug pair that can promote blood circulation, remove blood stasis, and treat tumors in clinics. The aim of the present study was to investigate the therapeutic material basis and potential mechanisms of CR-SR, CR, and SR for the treatment of liver cancer.Method: The chemical profile analyses of CR-SR, CR, and SR were performed by molecular networking and UPLC-LTQ-Orbitrap MSn. The anti-liver cancer activities of CR-SR, CR, and SR were assessed by using a zebrafish xenograft model in vivo for the first time and detected by the HepG2 cell model in vitro. Combining the network analysis and molecular docking, real-time quantitative polymerase chain reaction (RT-qPCR) experiments were undertaken to further explore the mechanisms of CR-SR, CR, and SR for the treatment of liver cancer.Results: In total, 65 components were identified in CR-SR, CR, and SR. Based on the clusters of molecular networking, a total of 12 novel diarylheptanoids were identified from CR-SR and CR. By combining our results with information from the literature, 32 sesquiterpenoids and 21 cyclic dipeptides were identified from CR-SR, CR, and SR. The anti-liver cancer activities were observed in both the drug pair and the single botanical drugs in vitro and in vivo, and the order of activity was CR-SR > CR > SR. They could downregulate the expression of proto-oncogene tyrosine-protein kinase Src (SRC), epidermal growth factor receptor (EGFR), estrogen receptor-α (ESR1), prostaglandin endoperoxide synthase 2 (PTGS2), and amyloid precursor protein (APP).Conclusion: Taken together, the present study provided an experimental basis for the therapeutic material basis and potential molecular mechanisms of CR-SR, CR, and SR. This study provided a novel insight for objective clinical treatment of liver cancer.